Pengaruh Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Dengan Kepuasan Konsumen Sebagai Variabel Intervening Pada Store Wardah Irian Tanjung Morawa Deli Serdang - Risa Ariyati; Yulia Tiara Tanjung; Nilvi Audia Harahap (Journal on Education, 2023)
Wardah is a beauty brand that cares and understands every woman's desire to always feel calm and comfortable with her appearance. The purpose of this research is to find out whether there is a close relationship between brand image and product quality in determining the level of buyers' purchasing decisions in order to survive in a competitive market, especially in the Deli Serdang district, Tanjung Morawa subdistrict. The approach used in this research is a quantitative approach. This type of research is associative, where research aims to determine the relationship between two or more variables. This research took place in Medan City, Deli Serdang Regency, Tanjung Morawa District, the objects studied were female consumers at the Wardah Irian Tanjung Morawa supermarket store. The population in this research was all consumers of Wardah cosmetic products in Tanjung Morawa District, totaling + 3000 purchases. in every month. sample size of 69 respondents. Data collection in this study was a questionnaire with a Likert scale. To fill in the questionnaire, respondents were asked to give an opinion about a series of statements related to the object under study. The test tool used was the SPSS program application 29. The results of this research are that there is an indirect influence of brand image on product quality. Consumer satisfaction on purchasing decisions has a significant influence on purchasing decisions at Wardah at the Irian Tanjung Morawa Store. Brand Image has a direct and significant influence on Consumer Satisfaction at Wardah at the Irian Store. Tanjung Morawa, Product Quality has a direct and significant effect on Consumer Satisfaction with Wardah at the Irian Tanjung Morawa Store. Buyer decisions have a direct and significant effect on consumer satisfaction with Wardah at the Irian Tanjung Morawa Store. Directly, brand image and product quality on consumer satisfaction through buyer decisions have a significant influence on consumer decisions on Wardah Cosmetics at the Irian Tanjung Morawa Store.